Design of Ergonomic Adjustable Welding Work Facilities Using the DFMA Method - Noveldi, Ahmad; Faisal Ashari; Rio Chandra Pratama (Journal of Information System, Technology and Engineering, 2023)
In this modern and sophisticated era, the manufacturing industry is developing both service industries and those that produce products with a variety of shapes and models to attract customers. For example, adjustable welding tables, motorbikes, cars, and others. Companies compete with each other in terms of price, product excellence, product innovation, and product convenience in order to find the right consumer market. DFMA (Design for Manufacturing and Assembly) is a method of making products that aims to facilitate the manufacturing and assembly process where existing designs can be simplified and adapted to the capabilities of the manufacturing facility by considering technical aspects. The scope of design and ergonomics activities includes problems related to human needs, including interior design, furniture design, environmental equipment design, transportation equipment design, textile design, graphic design, etc. (Setiawan, M. S. 2022). At this stage, data collection is carried out, and the author needs to design an adjustable welding table. However, first recompose the table components and determine which are assembly parts and subassembly parts. Then identify each component. Product size and components, labor time, manufacturing data, and others to support research. 1. Analysis of Design Needs 2. Preliminary Design Sketching 3. Design Evaluation 4. Final Design Refinement 4. Final Design Refinement 4. Final Design Refinement 4. Final Design Refinement 4. Final Design Refinement 4. Final Design Refinement. 1) In the previous product development, design 3 was completed with a design that is certainly more ergonomic than design 1, because design 3 has been adjusted to body size using ergonomic standards. 2) Based on the results of the development of this adjustable welding table product, option 3 is the one with the lowest cost because it has a smaller number of components and total assembly steps compared to options 1 and 2. The cost of option 1 is around Rp. 1,780,000; option 2 is around Rp. 1,515,000; and option 3 is around Rp. 870,000. The total assembly steps for option 1 are 40; option 2 is 34; and option 3 is 25. The number of components in options 1 and 2 is 10, while option 3 is only 9.